Truck platooning impact on existing Bridges' load ratings. (May 2023) - Elshazli, Mohamed T.; Ibrahim, Ahmed; Abdel-Rahim, Ahmed
Abstract: Implementation of Autonomous and Connected Trucks (ACTs) will have major impacts on mobility, safety, and infrastructure service life. Although truck platooning will increase fuel efficiency and improve transportation services, the platooning configuration is expected to accelerate damage to the existing infrastructure. This damage, if accumulates, will cost the country billions of dollars to fix and will affect the mobility of people and goods. This study aimed to develop a well-defined framework for assessing and a data-driven solution for addressing the impact of truck platoons on existing bridges in order to be prepared for future implementation of ACT and to preserve the current bridge inventory. An extensive parametric study of 29, 600 computer simulations was conducted to address the effect of a wide range of platooning configurations on the load rating of existing bridges using three different load rating methodologies (ASR, LFR, LRFR). The findings were then used to develop engineering guidelines that engineers can use to find the optimum parameters for any bridge case. The study also provided a potential implementation methodology that bridge owners can use to evaluate existing bridges for regular truck platooning applications. The number of trucks and their spacing have been shown to be critical parameters influencing bridge load ratings. Bridges rated using ASR or LFR have experienced a reduction in their rating factors for bending moments and shear forces. On the other hand, LRFR bridges have shown better results, especially for short spans and widely spaced trucks. Finally, the developed design charts were used to find the change in the load rating of a bridge case study and compared to AASHTO load ratings' equations; the results obtained were identical.